Evaluation of post-infectious inflammatory reactions in a retrospective study of 3 common invasive bacterial infections in pediatrics. Issue 38 (23rd September 2022) - Abraham, Pauline; Marin, Gregory; Filleron, Anne; Michon, Anne-Laure; Marchandin, Hélène; Godreuil, Sylvain; Rodière, Michel; Sarrabay, Guillaume; Touitou, Isabelle; Meslin, Pauline; Tournier, Carine; Van de Perre, Philippe; et al.
Abstract : Infectious diseases can result in unanticipated post-infectious inflammatory reactions (PIIR). Our aim was to explore PIIR in 3 frequent pediatric bacterial invasive infections in France by a retrospective monocentric study. We included children hospitalized between 2003 and 2012 for Streptococcus pneumonia e (SP), Neisseria meningitidis (NM), or Streptococcus pyogenes invasive infections. The PIIR had to have occurred between 3 and 15 days without fever despite an individually tailored antibiotic therapy. A descriptive analysis was carried out to determine PIIR risk factors. We included 189 patients, of whom 72, 79, and 38 exhibited invasive infections caused by S pyogenes, SP, and NM, respectively. The mean age was 44 months. PIIR were observed in 39 cases, occurring after a median of 8 days (5–12), with a median duration of 3 days (2–6). Fever, arthritis, and pleural effusion were observed in 87%, 28.2%, and 25.6%, respectively. In multivariate analysis, PIIR were associated with pleuropneumonia, hospitalization in an intensive care unit (ICU), and elevated C-reactive protein (CRP). PIIR were observed in 20% of children after SP, NM, or S pyogenes invasives infections. Their occurrence was associated with the initial severity but not the etiological microorganism. Further studies are warranted to confirm these findings.